“Sacris superis initiati canunt”: the idea of selectness in the decoration of the Strozzi Chapel in the Basilica of Santa Maria Novella in Florence - Lopukhova, Marina A. (Actual Problems of Theory and History of Art, 2012)
The author analyzes the principal motives of the Strozzi Chapel frescoes in Santa Maria Novella church in Florence, created by Filippino Lippi in 1489–1502. A concept of the patron’s selectness is clearly conveyed and emphasized by the form and position of his funeral monument, nature of the inscriptions and the choice of the Patriarchs as the theme of the ceiling decoration. A particular attention is given to the theme of glorification through learning that is revealed by painted figures of the Muses.
Keywords: Italian art; mural paintings; Early Renaissance; Florence; Filippino Lippi